Thomas & friends. Signals crossed [videorecording (DVD)]. (Universal Studios Home Entertainment, 2014)
Rumbling rails! Thomas & friends deliver mix-ups and mischief as signals get crossed on the Island of Sodor. Thomas digs Marion out of a deep hole, while Timothy helps Bill and Ben with coal trouble. Toby gets his signals confused at Knapford Junction, as Duncan blows steam dealing with a grumpy passenger. Thomas, Annie, and Clarabel put on the brakes when a passenger causes confusion and delay.